Strategi Pembelajaran Kooperatif Tipe Jigsaw Versus Pembelajaran Langsung - Mashudi (Edudeena : Journal of Islamic Religious Education, 2018)
Abstract: Learning method or technique and learning strategy need to be notice in learning activities. This study aim to discusses cooperative strategy. Cooperative strategy has some elements; (1) Positif depending to each other (2)face to face meeting (3) individual responsibility (4) group and interpersonal skill (5) effective group process. Some of the cooperative learning basic theories are Behaviourism theory and constructivism theory that have differ point of view. Benefit of cooperative learning could be divided into four aspects (1) improving positive attitudes toward learning activities (2) Increasing student interaction to each other (3) improving student learning achievement ,(4) authentic assessment. Then, Jigsaw in cooperative learning is a product of social constructivism. Slavid stated technique that use appropriate approach based on social cohesive are Jigsaw, Group Investigation and learning Together (LT).   Abstrak: Salah satu masalah yang memerlukan perhatian dalam kegiatan pembelajaran adalah metode teknik, dan strategi pembelajaran (learning metbod &technique). Strategi pembelajaran kooperatif memiliki beberapa elemen antara lain; (1) Saling ketergantungan positif, (2) Tatap muka, (3) Tanggung jawab individu, (4) Keterampilan kelompok dan interpersonal, dan (5) Keefektifan proses kelompok. Teori yang mendasari pembelajaran kooperatif dengan mengikuti perspektif yang berbeda. Di antaranya adalah teori behavioristik dan teori konstruktivisme. Manfaat pembelajaran kooperatif dilihat dari empat aspek tersebut; (1)Meningkatkan sikap positif terhadap kegiatan pembelajaran, (2)Menggiatkan interaksi antarsiswa, (3)Meningkatkan prestasi belajar, dan (4)Penilaian otentik. Berikutnya Pembelajaran kooperatif tipe jigsaw adalah produk dari perspektif konstruktivisme sosial. Sebagaimana Slavin menyebutkan teknik yang menggunakan pendekatan yang sesuai dengan pandangan kohesif sosial adalah Jigsaw, Group Investigation, dan Learning Together (LT).